'Watching the Waters': Tropic flows in the Harlem Renaissance, Black Internationalism and other currents. (21st September 2018) - Peake, Jak
Abstract : The 'Harlem Renaissance' is now a dominant term for what is commonly used to describe a cultural movement that emerged between the First and Second World Wars. The term became the hegemonic around the early 1970s, displacing similar, yet distinct, alternatives including the New Negro, the New Negro movement and the Negro/Black Renaissance. This essay traces a genealogy of such terms, metanarratives and historiographical currents. The aim here is to demonstrate how the hegemony of the term Harlem Renaissance is linked to its institutionalization as a subject and the rise of Black studies in the United States. The weighting of Harlem as a geographical reference point both localized and nationalized the subject area which resulted in a selective historiography and diminished the transnational dimensions of the New Negro and the Negro Renaissance. The framework is trans-American and the scope transnational, while the chronology covers an inner 1890s–1940s period, and a broad outer period which begins in 1701 and spans post-WWII writing. In marking these flows, this essay problematizes the notion of distinct political or cultural channels of the 'movement' or 'movements'. Recent scholarship attentive to some of the limitations of earlier Harlem Renaissance studies has illustrated the intertwined relationship of political, often radical, and artistic-aesthetic aspects of early twentieth-century black cultural activity and the key role played by Caribbeans. Drawing on these insights, this essay outlines that the transnational aspects of a black-centred cultural phenomenon have been better understood through a greater emphasis on Caribbean cross-currents.